Long term persistent accumulation of CD8+ T cells in synovial fluid of rheumatoid arthritis. Issue 10 (1st October 1997) - Masuko-Hongo, Kayo; Sekine, Taichi; Ueda, Shinichiro; Kobata, Tetsuji; Yamamoto, Kazuhiko; Nishioka, Kusuki; Kato, Tomohiro
Abstract : OBJECTIVE: To characterise the type and kinetics of T cell clones in synovial lesions of patients with rheumatoid arthritis (RA). METHODS: Mononuclear cells from serial samples of synovial fluid (SF) and peripheral blood from nine RA patients were separated phenotypically using antibody coated magnetic beads. After mRNA preparation, reverse transcription-polymerase chain reaction (RT-PCR) was performed to amplify V-D(N)-J (that is, the third complementarity determining, CDR3) regions of their T cell receptor beta chain genes. This was followed by single strand conformation polymorphism (SSCP) analysis to detect the clonotypes of accumulating T cells. Amino acid sequences of the dominant clones were also determined. RESULTS: Although peripheral T cells were heterogeneous, accumulation of oligoclonal T cells was detected in SF. The predominant accumulating clone was the CD8 subset, which was persistently present in serial samples obtained over almost one year of follow up. A proportion of these cells expressed CD25 or CD45RO, or both, suggesting they are 'memory' clones. CONCLUSION: The persistent presence of CD8+ T cell clones in RA joints indicates that they may be involved in the perpetuation of the chronic inflammatory process in RA joints.